2009
DOI: 10.1088/0953-8984/21/40/406005
|View full text |Cite
|
Sign up to set email alerts
|

The role of thermal coupling on avalanches in manganites

Abstract: We report here a study on the environmental dependence of the occurrence, at low temperature, of ultra-sharp field induced avalanches in phase separated manganites. Despite the high reproducibility of avalanches, it has already been observed that the critical fields shift with the magnetic field sweep rate and that different sample sizes lead to different ignition fields for the avalanches. Critical growing rates have been suggested to describe the avalanche ignition though the role of thermal coupling has har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…This process is driven by the heat conductance and it closely resembles the magnetic deflagration observed in molecular magnets and manganites. [22][23][24][25][26][27][28][29] The dependence of avalanches on the initial state, initial temperature, and magnetic field agrees with the theory of deflagration. 30 Since magnetic transition in Gd 5 Ge 4 also involves structural transformation, it represents an interesting example of the magnetostructural deflagration.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This process is driven by the heat conductance and it closely resembles the magnetic deflagration observed in molecular magnets and manganites. [22][23][24][25][26][27][28][29] The dependence of avalanches on the initial state, initial temperature, and magnetic field agrees with the theory of deflagration. 30 Since magnetic transition in Gd 5 Ge 4 also involves structural transformation, it represents an interesting example of the magnetostructural deflagration.…”
Section: Discussionsupporting
confidence: 76%
“…This avalanche-like process, that occurs when the field reaches a certain value, has striking similarity with avalanches observed in the magnetization curves of molecular magnets [15][16][17][18] and of some manganites. [19][20][21] The latter avalanches have been investigated and successfully described [22][23][24][25][26][27][28][29] within theory of magnetic deflagration. 30 Deflagration is a physical term for slow burning that occurs, e.g., in a combustion engine when a chemical reaction in the fuel-air mixture is ignited by a spark of fire.…”
Section: Introductionmentioning
confidence: 99%
“…The latent heat data, shown in figures 5 and 6, have been taken on a 100 µm size fragment, acquired in vacuum to ensure weak thermal linkage to the bath. It is interesting to acknowledge that different thermal environments may change the observed dynamics of the transition [22][23][24]. Precisely how the thermal environment influences the measurements described here will be the subject of future studies.…”
Section: T)mentioning
confidence: 93%
“…6 Historically, such magnetic discontinuities have been called magnetic avalanches and they have been also observed in other materials [21][22][23][24][25][26][27][28] which also exhibit a giant magnetocaloric effect 24,29 related to a transition from a kineticallyarrested state to magnetic equilibrium 4,30 . The dynamics of the magnetization of the sample during such transitions have been reported first in molecular magnets [31][32][33][34][35][36][37][38][39] , and later in manganites [40][41][42] and polycrystalline samples of Gd 5 Ge 4 43 . For all these materials it was found that a phase-transition front forms and burns as a consequence of the energy difference between the initial and final states involved, and then it propagates through the sample at a constant speed on the order of a few m/s according to a heat diffusion process (see Appendix A for the basics of the theory of this phenomenon 44 and the definition of the different physical magnitudes involved).…”
Section: Introductionmentioning
confidence: 97%